2018
DOI: 10.26508/lsa.201800111
|View full text |Cite
|
Sign up to set email alerts
|

Identification ofPlasmodiumGAPDH epitopes for generation of antibodies that inhibit malaria infection

Abstract: This study reports on the identification of two Plasmodium GAPDH epitope peptides that are responsible for sporozoite–Kupffer cell interaction and act as antigens against malaria infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Murine parasite species and Pf required the receptor CD68 (scavenger receptor D1) to enter Kupffer cells in vivo and in vitro [56]. A candidate to interact with CD68 is the Pb GAPDH (glyceraldehyde 3-phosphate dehydrogenase) [57].…”
Section: Box 2 Biogenesis and Exocytosis Of Micronemes And Rhoptries In Sporozoitesmentioning
confidence: 99%
“…Murine parasite species and Pf required the receptor CD68 (scavenger receptor D1) to enter Kupffer cells in vivo and in vitro [56]. A candidate to interact with CD68 is the Pb GAPDH (glyceraldehyde 3-phosphate dehydrogenase) [57].…”
Section: Box 2 Biogenesis and Exocytosis Of Micronemes And Rhoptries In Sporozoitesmentioning
confidence: 99%
“…Another example is Romiplostim (Nplate®), a thrombopoietin receptor agonist used to treat thrombocytopenia ( Cwirla et al, 1997 ; Keating, 2012 ; Tarantino et al, 2019 ). The phage display approach led to the identification of a peptide that structurally mimics glyceraldehyde-3-phosphate dehydrogenase (GAPDH) on the surface of Plasmodium sporozoites; this peptide became a new vaccine candidate for targeting malaria liver invasion ( Cha et al, 2016 , 2018 ). The phage display approach was used to search for mimotopes of the Trypanosoma brucei variant surface glycoprotein (VSG).…”
Section: Discussionmentioning
confidence: 99%
“…Entry of the host cell is essential to complete the parasite’s life cycle and infection spread, thus this is a promising target for the development of new therapeutic strategies ( Walker et al, 2013 ). In this work, we used the same phage library that was used to identify a GAPDH ligand molecule on the surface of the invasive Plasmodium sporozoite ( Cha et al, 2016 , 2018 ). Here we showed that the N3 peptide binds to the T. cruzi invasive forms ( Lima et al, 2010 ; Salassa and Romano, 2018 ) and importantly, by doing so, inhibits target cell infection.…”
Section: Discussionmentioning
confidence: 99%
“…Mice were immunized twice at 2-week intervals. Serum was collected 14–21 days after administration of the last booster ( Cha et al, 2018 ).…”
Section: Methodsmentioning
confidence: 99%